Penanggulangan Pornografi dalam Mewujudkan Manusia Pancasila - Dewi Bunga (Jurnal Konstitusi, 2011)
The provisions concerning  the  prohibition  of  pornography  are  set in the national legal instruments and instruments of international law. Specifically regulated in Law no. 11 Year 2008 About  Pornography  whose  existence  was  confirmed  by  the  Constitutional  Court  Decision No. 10-17-23/PUU-VII/2009 who rejected the  judicial  review  of  Law no. 44 Year  2008 on Pornography seeing this legislation is still needed to protect public morality. Prohibition of pornography  is  also  in  line with the principle of the 2nd Pancasila who want a  civilized  human being. However, the existence of the rule is not effective in preventing pornography, especially with the internet presence that can expand and facilitate access to pornography. Therefore it is necessary efforts to control pornography in the human form of Pancasila.